Nightmare in angel city - Dixon, Franklin W. (Pocket Books New York, 1988)
Nightmare in Angel City is a thrilling suspense novel that follows the story of a young woman, Emma, who moves to Angel City in search of a fresh start. However, her hopes for a new beginning quickly turn into a nightmare when she becomes entangled in a series of mysterious disappearances and a dark underworld of crime. As she investigates the chilling events, Emma uncovers secrets about the city and its inhabitants, revealing a sinister connection to her own past. The novel explores themes of fear, resilience, and the quest for truth, leading to a heart-pounding climax that will keep readers on the edge of their seats.